Accident analysis: front, side and rear protection of trucks. (5th August 2014) - Hogstrom, K.; Svensson, L.
The Volvo Truck Corporation Accident Commission has carried out intensive analyses of over 1000 truck accidents since it was set up in 1970. Safety measures that have been introduced by Volvo are outlined in this paper, in particular those to minimise fatalities and injuries in side impacts between trucks and motorcyclists, and front and rear impacts between trucks and cars. Protective measures for truck drivers are discussed. Including energy–absorbing dashboards and steering wheels and a new type of inertia roller seat belt.